2019
DOI: 10.1101/751909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pumilio Proteins Exert Distinct Biological Functions and Multiple Modes of Post-Transcriptional Regulation in Embryonic Stem Cell Pluripotency and Early Embryogenesis

Abstract: Gene regulation in embryonic stem cells (ESCs) has been extensively studied at the epigenetic-transcriptional levels, but not at the post-transcriptional levels. Pumilio (Pum) proteins are among the few known translational regulators required for stem cell maintenance in invertebrates and plants. Here we report the essential function of two murine Pum proteins, Pum1 and Pum2, in ESCs and early embryogenesis. Pum1/2 double mutants are developmentally delayed at the morula stage and lethal by embryonic day 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…S4a). In the top ten results of principal component analysis (PCA) of the 163 transcription factors, stemness-related PUM1 [ 46 , 47 ], CLOCK [ 48 ], SP1, and TCF12 played a major positive regulatory role in PCa cell stemness (Fig. 3 b and Additional file 8 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4a). In the top ten results of principal component analysis (PCA) of the 163 transcription factors, stemness-related PUM1 [ 46 , 47 ], CLOCK [ 48 ], SP1, and TCF12 played a major positive regulatory role in PCa cell stemness (Fig. 3 b and Additional file 8 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4a). In the top ten results of principal component analysis (PCA) of 163 common transcription factors, it was found that stemness-related PUM1 [46,47], CLOCK [48], SP1, and TCF12 played a major positive regulation role on PCa cell stemness (Fig. 3b and Supplementary Fig.…”
Section: The Cnv Of Stemness-related Genes Elevated In Prostate Cancermentioning
confidence: 99%
“…4a). In the top results of principal component analysis (PCA) of 253 common transcription factors, it was found that stemness-related PUM1 [44,45], CLOCK [46], SP1 and TCF12 played a major positive regulation role on PCa cell stemness, while IRF3 [47] was a negative correlation with other 9 transcription factors and played negative regulation role on PCa cell stemness (Fig. 3b, Supplementary Fig.…”
Section: Correlation Analysis Between Cancer Cell Stemness and Clinical Grade In Prostate Cancermentioning
confidence: 99%